Penerapan METODE DEMONSTRASI LAGU “YAMKO RAMBE YAMKO” PADA KELOMPOK PADUAN SUARA KIDUNG ARUTALA SMA NEGERI 1 WARU SIDOARJO - martynda elfrida; Senyum Sadhana (Universitas Negeri Surabaya, 2024)
This study aims to analyze the application of the demonstration method in the Kidung Arutala choir practice at Waru Sidoarjo State High School 1, specifically regarding the song “Yamko Rambe Yamko.” The research focuses on the process of applying the demonstration method, the achievement of choir members’ practice outcomes in the behavioral, affective, and psychomotor domains, as well as the challenges faced during the practice process. This study employs a qualitative approach using a descriptive method. The research subjects are the members of the Kidung Arutala choir and the choir director. The research object is the application of the demonstration method within the context of choir practice. Data collection techniques include observation, interviews, documentation, and literature review. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques, and their validity was tested through source and technique triangulation. The results of the study indicate that the application of the demonstration method is capable of increasing the activity, engagement, and understanding of choir members regarding vocal and musical techniques. The research subjects were participants who were actively involved in the training process through observing, imitating, and directly practicing the techniques demonstrated by the trainer. The training results showed improvement in three domains of learning: the behavioral domain (changes in students’ attitudes after applying the demonstration method), the affective domain (attitudes of discipline, cooperation, and responsibility), and the psychomotor domain (articulation skills, breath control, intonation, and musical expression). During the demonstration process, the coach provided step-by-step guidance, repeated demonstrations, and both individual and group approaches. Thus, the application of the demonstration method in rehearsals for the song “Yamko Rambe Yamko” proved effective in improving the vocal and musical abilities of the members of the Kidung Arutala choir. This study is expected to serve as a reference for coaches or arts and culture teachers in developing more effective, practical, and contextual vocal teaching methods.